(untitled) (LACCEI, 2024)
Over the years, the exponential increase in CO2 emissions has contributed to climate change. Currently, new technologies at the industrial level have been applied to decrease the carbon footprint, reducing the negative impact of CO2 on the environment. The oil industry joins the change through the enhanced oil recovery (EOR) process using CO2 as an injection fluid. The study proposes a theoretical model based on a literature review using the PRISMA methodology, in order to evaluate and compare the effects of CO2 in gas and foam phase on the different rock/fluid properties during an enhanced oil recovery operation. Initially, a sample of 300 scientific articles was obtained from the Scopus web platform, of which 114 articles were selected by applying the PRISMA methodology for the development of the study. In general, the present study contributes to the literature by demonstrating that the use of the PRISMA methodology in a literature review allows obtaining reliable and updated information. The results of the comparative, qualitative and quantitative analysis showed that in the process of CO2 injection as gas or foam, changes in the properties of the rock and fluids occur both at reservoir level in pilot tests and in laboratory experiments.